A comparative study of compositions and microstructures of two types internal-tin process Nb3Sn wires. (September 2020) - Zhang, Hengcheng; Huang, Chuanjun; Huang, Rongjin; Li, Laifeng
Highlights: The internal 3D-view of two Nb3 Sn strands were detected with a non-destructive way, high-resolution 3D X-ray micro tomography. The Nb3 Sn phase of WST strand has a poor crystallinity with high defect density and the filaments of OST strand were connected forming a large Nb3 Sn bundle. The higher Jc of the OST strand than that of the WST is ensured not only by the overall Nb3 Sn layers thickness, but also by smaller grain sizes and narrower zone of columnar grains. Abstract: In the present work, microstructural and microchemical of Nb3 Sn strands with the internal tin process produced by the Western Superconductor Technology co., Ltd (WST) and Oxford Instruments co., Ltd (OST) were analyzed. The internal 3D-view of two Nb3 Sn strands were detected with a (sub-)micrometric resolution in a non-invasive, non-destructive way, i.e. high-resolution 3D X-ray micro tomography. The distribution of filaments and voids induced by the functional heat treatment of two strands were investigated. The elements distribution after heat reaction of two strands was investigated through elemental mapping by scanning electron microscope (SEM) and energy dispersive X-ray analysis. The filaments of the WST Nb3 Sn strand distributed uniformly, whereas the filaments separated with clear copper boundary among filaments. However, the filaments of the OST Nb3 Sn strand have serious overlap phenomenon and the copper isolation interface was not clear among filaments. In order to investigate the distinction of microstructure, the selected area electron diffraction was also performed by transmission electron microscopy (TEM) and the results indicated that obvious impurities were observed in the Nb3 Sn phase of the WST strand compared to the OST strand.